Skating start propulsion: three-dimensional kinematic analysis of elite male and female ice hockey players - Shell, J. R.; Robbins, S. M. K.; Dixon, P. C.; Renaud, P. J.; Turcotte, R. A.; Wu, T.; Pearsall, D. J. (Sports Biomechanics, 2017)
The forward skating start is a fundamental skill for male and female ice hockey players. However, performance differences by athlete's sex cannot be fully explained by physiological variables; hence, other factors such as skating technique warrant examination. Therefore, the purpose of this study was to evaluate the body movement kinematics of ice hockey skating starts between elite male and female ice hockey participants. Male (n=9) and female (n=10) elite ice hockey players performed five forward skating start accelerations. An 18-camera motion capture system placed on the arena ice surface captured full-body kinematics during the first seven skating start steps within 15meters. Males' maximum skating speeds were greater than females. Skating technique sex differences were noted: in particular, females presented ~10° lower hip abduction throughout skating stance as well as ~10° greater knee extension at initial ice stance contact, conspicuously followed by a brief cessation in knee extension at the moment of ice contact, not evident in male skaters. Further study is warranted to explain why these skating technique differences exist in relation to factors such as differences in training, equipment, performance level, and anthropometrics. ABSTRACT FROM AUTHOR